Primary Venous Valve Disease - Rachuk, Dmytro (European Journal of Scientific Exploration, 2018)
The human body is a complex system and each organ must receive enough blood and oxygen that is transported through in blood through blood vessels. At the moment, despite the fact that medicine is widely developing in the world, more and more people have diseases of the cardiovascular system. In the scientific work we will consider the primary diseases of the human venous valve and analyze the function and importance of venous valves and the vascular system as the most important system for the normal functioning and vital activity of the human body. It is also necessary to identify the main diseases and problems that may arise in this vascular system and the possible ways of solving these problems and treatment of diseases associated with the venous valve.